2010
DOI: 10.1007/s00441-010-0977-5
|View full text |Cite
|
Sign up to set email alerts
|

LPA receptor expression in the central nervous system in health and following injury

Abstract: Lysophosphatidic acid (LPA) is released from platelets following injury and also plays a role in neural development but little is known about its effects in the adult central nervous system (CNS). We have examined the expression of LPA receptors 1-3 (LPA(1-3)) in intact mouse spinal cord and cortical tissues and following injury. In intact and injured tissues, LPA(1) was expressed by ependymal cells in the central canal of the spinal cord and was upregulated in reactive astrocytes following spinal cord injury.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 50 publications
3
24
2
Order By: Relevance
“…We recently described that LPAR 2,3 are weakly expressed in the adult mouse brain and are upregulated in response to injury (Goldshmit et al 2010). LPAR 2,3 were found to be very weakly expressed by ependymal cells in the uninjured mouse brain, a pattern that was not modified by injury (Goldshmit et al 2010). However, although we observed expression of LPAR 1 on myelinated fibers in the human brain, this was not observed in the adult mouse brain (Goldshmit et al 2010).…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…We recently described that LPAR 2,3 are weakly expressed in the adult mouse brain and are upregulated in response to injury (Goldshmit et al 2010). LPAR 2,3 were found to be very weakly expressed by ependymal cells in the uninjured mouse brain, a pattern that was not modified by injury (Goldshmit et al 2010). However, although we observed expression of LPAR 1 on myelinated fibers in the human brain, this was not observed in the adult mouse brain (Goldshmit et al 2010).…”
Section: Discussioncontrasting
confidence: 74%
“…The availability of specific commercial ATX antibodies for immunochemistry will be of great interest for the further study of ATX brain localization following TBI in particular within the corpus callosum. Alongside demonstration by others (Liszewska et al 2009), we previously showed specificity of the LPAR antibodies used in this study on tissue from the various LPARs knockout mice (Goldshmit et al 2010). Experiments described here further confirm specificity of LPAR 1 and LPAR 2 antibodies in human cells.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…10 Considering the pleiotropic effects of LPA in the brain along with the upregulation of LPAR1-3 after injury, it has been proposed that LPA may regulate essential aspects of cellular organization and have a crucial role in reactive astrogliosis, neural regeneration, and axonal regrowth. 25 Less is known about the role of LPAR4 and LPAR5 within the brain.…”
Section: Discussionmentioning
confidence: 99%
“…However, it needs to pay an attention to use plant-derived LPAs in pathophysiological conditions such as cancers of breast cancer, melanoma, and ovarian cancer, since autotaxin activity is increased in these cancer patients. 29) These examples might not be enough for pharmacological or clinical applications of plant-derived LPAs however. In the future, more studies on LPA-derived biological effects could expand the applications of herbal LPAs.…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%